The Process of Building Trust in Social Exchange Relationships between Influencers and KOL Specialists in Beauty Companies - Belicia Griselda Talahaturusun; Cicilia Larasati Rembulan (PSIKODIMENSIA Kajian Ilmiah Psikologi, 2025)
The exchange process between influencers and KOL (Key Opinion Leader) specialists in beauty companies involves complex stages. Trust is an important aspect to examine because, despite practical challenges often arising between influencers and KOL specialists. This study aims to identify the stages of the exchange process between influencers and KOL specialists in beauty companies and examine how trust is built at each stage. Using a qualitative method with an instrumental case study design, participants were selected through purposive sampling, consisting of three influencers and three KOL specialists. Data was collected through offline and separate interviews and analyzed using a thematic approach. The findings reveal three stages of the exchange process: the pre-collaboration stage, the collaboration stage, and the post-collaboration stage, which emphasizes relationship maintenance and evaluation of partnership outcomes. The study highlights that open, transparent, and professional communication is essential in fostering a positive exchange. Regarding trust, the study finds that social exchange involves both trust and distrust.